2022
DOI: 10.3389/fpsyg.2022.1019878
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between abuse and neglect and adolescent suicidality: A moderated mediation model

Abstract: Abuse and neglect can lead to suicide in adolescents; however, the internal mechanisms between abuse and neglect and suicidality remain unclear. We hypothesized that abuse and neglect could affect adolescent suicidality, and that mediating and moderating mechanisms exist between these two variables. We tested the mediating effects of stressful life events (misunderstanding and discrimination by others, poor academic performance, failed exams, interpersonal problems, and school punishment) on suicidal tendencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Previous research has shown that females tend to engage in contemplative responses and encode negative information more deeply, making it difficult for them to withdraw from negative events ( Hilt et al, 2010 ). Females are less psychologically resilient than males, but they are more relationship-oriented and can get more companionship and emotional support from their peers and teachers in addition to their parents ( Zhang et al, 2022 ). Based on the expansion and construction theory of positive emotions ( Fredrickson, 2001 ), sense of hope can help females reduce negative emotional distress by constructing psychological resources that give them more confidence to believe in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that females tend to engage in contemplative responses and encode negative information more deeply, making it difficult for them to withdraw from negative events ( Hilt et al, 2010 ). Females are less psychologically resilient than males, but they are more relationship-oriented and can get more companionship and emotional support from their peers and teachers in addition to their parents ( Zhang et al, 2022 ). Based on the expansion and construction theory of positive emotions ( Fredrickson, 2001 ), sense of hope can help females reduce negative emotional distress by constructing psychological resources that give them more confidence to believe in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Mental toughness, as an important indicator to resist external stress, can give timely defusion and recovery to maintain a good mental state when encountering setbacks ( 43 ). Research has shown that psychological resilience can improve individuals’ negative emotions in the face of adversity and can serve as an internal defense mechanism to regulate SSIB ( 44 ). And high-level resilience increases the resistance to negative emotions precisely when college athletes infected with COVID-19 engage in distress rumination, allowing them to confront this public health emergency.…”
Section: Discussionmentioning
confidence: 99%
“…13 A study involving 5,852 adolescents from 37 middle schools in 5 provinces in China demonstrated a relationship between abuse, neglect, and suicide in adolescents. 15 Research conducted in the Philippines has identified several factors that increase the risk of attempted suicide, including the female gender, physical attacks, bullying, loneliness, poor sleep, limited close friends, smoking, alcohol use, low physical activity, amphetamine or methamphetamine use, and low parental supervision. 16 In a study by Chan YY et al, which examined 2,789 school-going adolescents aged 16-17 in Malaysia, the findings revealed that the female gender, feelings of loneliness and anxiety, a lack of close friends and peer support, engagement in sexual intercourse, and involvement in fights were associated with a higher risk of SI.…”
Section: Introductionmentioning
confidence: 99%